2018
DOI: 10.1371/journal.pone.0206552
|View full text |Cite
|
Sign up to set email alerts
|

Methylation dependent down-regulation of G0S2 leads to suppression of invasion and improved prognosis of IDH1-mutant glioma

Abstract: Isocitrate dehydrogenase (IDH) mutations are a prognostic factor in diffuse glioma. However, the mechanism by which these mutations improve prognosis are not clear. In a subset of IDH-mutant glioma, remodeling of the methylome results in the glioma-CpG island methylator phenotype (G-CIMP) and transcriptional reorganization. In this study, we focus on G0/G1 switch 2 (G0S2), which is highly downregulated in G-CIMP glioma. We found that G0S2 expression tended to increase as the WHO grade increased, and G0S2 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…By analyzing The Cancer Genome Atlas (TCGA), Fukunaga et al showed that pateients in the higher G0S2 expression group had a poorer prognosis [18]. They also demonstrated that G0S2 expression levels were higher in recurrent tumor specimens that that at the initial diagnosis in the same patients [18]. Here in this study, we show that G0S2 promotes tumor growth in gliomas.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…By analyzing The Cancer Genome Atlas (TCGA), Fukunaga et al showed that pateients in the higher G0S2 expression group had a poorer prognosis [18]. They also demonstrated that G0S2 expression levels were higher in recurrent tumor specimens that that at the initial diagnosis in the same patients [18]. Here in this study, we show that G0S2 promotes tumor growth in gliomas.…”
Section: Discussionsupporting
confidence: 61%
“…Although Zagani et al [43] demonstrated that Eμ-Myc transgenic mouse model was not the correct model to conduct studies on G0S2, they found deletion of the G0S2 gene in mice did not show any effect on the latency of cancer progression in the Eμ-Myc model of lymphoma [43]. By analyzing The Cancer Genome Atlas (TCGA), Fukunaga et al showed that pateients in the higher G0S2 expression group had a poorer prognosis [18]. They also demonstrated that G0S2 expression levels were higher in recurrent tumor specimens that that at the initial diagnosis in the same patients [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This influence could be relevant for the metabolic adaptation of cancer cells. However, preliminary studies have provided conflicting data on a role of G0S2 in cancer cells [34,[52][53][54]. Our discovery about the existence of strong correlations between G0S2 levels and patients' survival in different cancers suggests the needing of a more extensive investigation about the impact of this gene on the metabolism and proliferation of transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…IDH mutations that produce 2-hydroxyglutarate can cause EMT in colorectal cancer cells through driving the expression of the transcription factor ZEB1 [89,91]. Conversely, IDH mutant gliomas can have better prognosis due to promotion of methylation and thereby suppression of invasion-promoting genes such as G0S2 [92].…”
Section: Metabolism and Epigenetic Regulation In Metastasismentioning
confidence: 99%